Foreign experience of state regulation of innovative projects at the regional level (Journal of Economic Research & Business Administration, 2016)
In this article the foreign experience of state regulation of innovativeprojects at the regional level. Comparative analysis of the experienceof developed countries shows that in many countries formed a countermovement«from the center to the regions» and «from the regions to thecenter.» There is a spontaneous process of searching for innovative modelsof regional development, while the process of the search model of innovativedevelopment «from above», at the level of national governments. Andif at the level of regions dominated by attempts to real action on the transferof development economics with virtually no experience with the formationof a model to be emulated in other regions, the level of federal centersdominate the discussion, debate, construction of theoretical models witha significant lack of real action in relation to the region in the direction ofhelping them to change the structure of their economies.
Keywords: innovation; region; state regulation; international experience; innovative project.